Creating a special outfit for spinning workers. - Khujayeva Malika Ergash kizi (Лучшие интеллектуальные исследования, 2024)
Annotation. This article explores the design and implementation of a special outfit tailored for workers in the spinning industry. It aims to address the unique challenges faced by spinning workers, including safety, comfort, and productivity. Through a detailed literature analysis, methodical design process, and comprehensive evaluation, this study presents the benefits and potential improvements of the proposed outfit.